2014
DOI: 10.1115/1.4028061
|View full text |Cite
|
Sign up to set email alerts
|

Selective Surface Roughness to Suppress Flow-Induced Motion of Two Circular Cylinders at 30,000 < Re < 120,000

Abstract: D epartm ent o f Naval A rch ite ctu re and M a rin e E n g in e erin g, U n iv e rs ity o f M ic h ig a n , A n n A rb o r, M l 4 8 1 0 5 e -m a il: h rp a rk @ u m ic h .e d u S e le c tiv e S u rfa c e R o u g h n ess to S u p p ress F lo w -In d u c e d M o tio n of T w o C irc u la r C y lin d e rs at 3 0 ,0 0 0 < R e < 1 2 0 ,0 0 0 M ic h a e l M . B e rn its a s 2 P ro fe sso r D epartm ent o f Naval A rc h ite c tu re and M a rin e E n g in e erin g, U n iv e rs ity o f M ic h ig a n , A n n A rb o r, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Application of PTC as a step on the cylinder returned satisfactory results with CFD in the TrSL3 flow regime. On the contrary, CFD results for smooth cylinders agree with experiments for lower Reynolds numbers only as Park et al (2014) suggested although a subsequent study of Kinaci et al (2016b) have shown that it is also possible to obtain good accordance with experimental results at even higher Reynolds numbers. Steven et al (2016) investigated the flow around an elastically mounted cylinder using LargeEddy Simulation (LES).…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Application of PTC as a step on the cylinder returned satisfactory results with CFD in the TrSL3 flow regime. On the contrary, CFD results for smooth cylinders agree with experiments for lower Reynolds numbers only as Park et al (2014) suggested although a subsequent study of Kinaci et al (2016b) have shown that it is also possible to obtain good accordance with experimental results at even higher Reynolds numbers. Steven et al (2016) investigated the flow around an elastically mounted cylinder using LargeEddy Simulation (LES).…”
Section: Introductionmentioning
confidence: 51%
“…In some studies such as (Ding et al, 2013;Wu et al, 2014;Park et al, 2014), it has been suggested that the boundary layer separation on a fixed cylinder at > 10000~12000 (some references say > 20000 ) cannot be predicted accurately which results in the failure of simulating numerically the smooth cylinders in VIV. Although this may partly be correct, it has been shown in this section that there is satisfactory accordance with experiments until the cylinder experiences drag crisis in the critical (near > 3 • 10 ) and the supercritical (around 3 • 10 < < 10 ) regions.…”
Section: Stationary Cylinder Case At High Reynolds Numbersmentioning
confidence: 99%
“…2.2 Physical V ck VIVACE System. By introducing passive turbulent control (PTC), the MRELab research team was able to reduce VIV [37,38] and at the same time to initiate galloping, and to achieve back-to-back VIV and galloping on a single circular cylinder [39]. The effects of PTC on multicylinder FIM were further studied experimentally by Kim et al [11] and using CFD by Ding et al [40,41].…”
Section: System Descriptionmentioning
confidence: 99%
“…Their experimental work includes extensive testing of cylinders with distributed sandpaper strips (Passive Turbulence Control/PTC). 4,5,7,11,[17][18][19][20] This approach proved to be effective in augmenting fluid induced motions as they observed galloping oscillations at high reduced velocities. Different types of galloping responses, hard galloping (requiring a threshold amplitude) and soft galloping (not requiring a threshold amplitude), were observed in their experiments depending upon the position of the rough strip.…”
Section: -3mentioning
confidence: 99%
“…One such harvesting device, which falls in the non-rotary class and exploits the phenomena of Fluid Induced Motion (FIM) of bluff bodies (especially Vortex Induced Vibration (VIV) and galloping), is called VIVACE (acronym for VIV for Aquatic Clean Energy) and was developed and patented by Professor Michael Bernitsas and co-workers at the University of Michigan. [4][5][6][7][8][9][10] The device converts the energy of river/tidal/ocean currents to mechanical energy by inducing free vibration of cylinders 6,11 and can be used in water bodies with current velocities as low as 1-2 m/s, as opposed to turbines which operate in currents with velocities > 2 m/s. A VIV based device is simple in construction and is modular, scalable, and robust and does not employ any rotating parts like turbines or propellers.…”
Section: Introductionmentioning
confidence: 99%